Group Norms Influence Children’s Expectations About Status Based on Wealth and Popularity - Yee, Kathryn M.; Glidden, Jacquelyn; Killen, Melanie (Frontiers in Psychology, 2022)
Children’s understanding of status and group norms influence their expectations about social encounters. However, status is multidimensional and children may perceive status stratification (i.e., high- and low-status) differently across multiple status dimensions (i.e., wealth and popularity). The current study investigated the effect of status level and norms on children’s expectations about intergroup affiliation in wealth and popularity contexts. Participants (N = 165; age range: 5-10 years; Mage = 7.72 years) were randomly assigned to hear two scenarios where a high- or low-status target affiliated with opposite-status groups based on either wealth or popularity. In one scenario, the group expressed an inclusive norm. In the other scenario, the group expressed an exclusive norm. For each scenario, children made predictions about children’s expectations for a target to acquire social resources. Novel findings indicated that children associated wealth status to some extent, but they drew stronger inferences from the wealth dimension than from the popularity dimension. In contrast to previous evidence that children distinguish between high- and low-status groups, we did not find evidence to support this in the context of the current study. In addition, norms of exclusion diminished children’s expectations for acquiring social resources from wealth and popularity groups but this effect was more pronounced in wealth groups. We found age differences in children’s expectations in regards to norms, but not in regards to status. The implications of how these effects, in addition to lack of effects, bear on children’s expectations about acquiring resources are discussed.